2005
DOI: 10.1093/jn/135.10.2299
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Decreases Oxidative Stress, NF-κB Activation, and iNOS Overexpression in Liver of Streptozotocin-Induced Diabetic Rats

Abstract: Increasing evidence in both experimental and clinical studies suggests that oxidative stress is involved in the pathogenesis and progression of diabetic tissue damage. This study investigated the protective effects of quercetin treatment on oxidative stress, nuclear factor (NF)-kappaB activation and expression of inducible nitric oxide synthase (iNOS) in streptozotocin-induced diabetic rats. Male Wistar rats were divided into 4 groups: control rats, control rats treated daily with quercetin (150 micromol/kg, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
187
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(212 citation statements)
references
References 57 publications
17
187
0
8
Order By: Relevance
“…Considering that, in a separate pharmacological study, each extract (leaf, stem, root and fruit) elicited a range of in vitro anti-diabetic activities (Martineau et al, 2006), it is interesting that all the identified classes of phenolic compounds, chlorogenic acid, quercetin derivatives, procyanidins and anthocyanins, have demonstrated anti-diabetic potential in vitro and in vivo (Hemmerle et al, 1997;Rodriguez de Sotillo and Hadley, 2002;Kim et al, 2003;Tsuda et al, 2003;Pinent et al, 2004;Ajay et al, 2005;Coskun et al, 2005;Dias et al, 2005;Jayaprakasam et al, 2006 …”
Section: Figurementioning
confidence: 99%
“…Considering that, in a separate pharmacological study, each extract (leaf, stem, root and fruit) elicited a range of in vitro anti-diabetic activities (Martineau et al, 2006), it is interesting that all the identified classes of phenolic compounds, chlorogenic acid, quercetin derivatives, procyanidins and anthocyanins, have demonstrated anti-diabetic potential in vitro and in vivo (Hemmerle et al, 1997;Rodriguez de Sotillo and Hadley, 2002;Kim et al, 2003;Tsuda et al, 2003;Pinent et al, 2004;Ajay et al, 2005;Coskun et al, 2005;Dias et al, 2005;Jayaprakasam et al, 2006 …”
Section: Figurementioning
confidence: 99%
“…Flavonoids can exert their antioxidant activity by various mechanisms, e.g., by scavenging or quenching free radicals, by chelating metal ions, or by inhibiting enzymatic systems responsible for free radical generation (Bláha et al 2004;Dias et al 2005). …”
mentioning
confidence: 99%
“…Oil producing seeds contain various types of phenolic compounds, such as flavonoids, lignans, lignins, phenolic acids, and tannins. Flavonoids can exert their antioxidant activity via a series of mechanisms, e.g., by chelating metal ions, by scavenging or quenching free-radicals or by inhibiting enzymetic systems responsible for free-radical generation (Dias et al, 2005;Islam, 2009). Flavonoids are the most widely present polyphenolic compounds in many oil seeds (Saikia et al, 2006).…”
Section: Phototoxicitymentioning
confidence: 99%